Evaluating the effectiveness of the rehabilitation program for treating the anterior cruciate ligament (ACL) in team sport athletes" (Football - Basketball - Handball) - Saad Shallak, Hassan; Abdul Hussein , Abbas Zaki; Sabah Nouri, Ali; Mohammed Al-Diwan , Lamyaa Hassan (مجلة دراسات وبحوث التربية الرياضية, 2025)
The aim of the study is to investigate the impact of surgical and non-surgical rehabilitation programs on anterior and posterior cruciate ligament (ACL) injuries in team sports athletes, such as football, basketball, and handball. The methodology used was the descriptive-analytical approach using objective measures. The study included a sample of 60 players aged between 18 and 30 years who had suffered a cruciate ligament injury. The sample was divided into two groups: one group underwent surgical rehabilitation after ACL reconstruction surgery, and another group underwent non-surgical rehabilitation through specialized therapeutic exercises. The researchers concluded that the study showed that surgical rehabilitation for ACL injuries was more effective in improving range of motion, reducing pain, and increasing muscle strength compared to non-surgical treatment. Additionally, the researchers recommended the necessity of designing specialized rehabilitation programs that consider the nature of the injury and the needs of each player to ensure the restoration of movement and safe return to competition